Analyzing Gender and Educational Differences in Mate Selection Preferences Among Indonesian Early Adults - Mira Ariyani; Lussy Dwiutami Wahyuni; Vanessa Maria Hamjay (AL-ISHLAH: Jurnal Pendidikan, 2025)
Mate selection is a key developmental task during early adulthood, shaped by sociocultural and individual factors. This study investigates how gender and educational background influence mate selection preferences among Indonesian early adults, a topic that remains underexplored in local contexts. A quantitative comparative approach was used, involving 300 unmarried Indonesian individuals aged 20–40, all of whom had at least a diploma (D3) or higher education. Data were collected using an adapted version of the Mate Preferences Questionnaire developed by Buss and Barnes. Non-parametric analyses (Mann–Whitney U and Kruskal–Wallis tests) were employed due to non-normal data distribution. Significant differences were found in mate selection preferences based on gender and education level. Men prioritized physical attractiveness, household management ability, and intelligence, while women favored financial stability, religiosity, and higher education. Educational background also influenced preferences: respondents with master’s degrees (S2) placed greater emphasis on religiosity and family background, while those with diploma/bachelor’s degrees (D3/S1) favored sociability and physical attractiveness. Interaction effects between gender and education showed additional variation across multiple criteria including income, intelligence, and household roles. These findings highlight how mate preferences among Indonesian early adults are shaped by both gender norms and educational attainment, reflecting the intersection of traditional cultural values with emerging social trends. The study underscores the importance of considering local sociocultural context in understanding mate selection dynamics and recommends culturally sensitive premarital education programs.